2016
DOI: 10.1016/j.biortech.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interspecific competition on the growth of macrophytes and nutrient removal in constructed wetlands: A comparative assessment of free water surface and horizontal subsurface flow systems

Abstract: The outcome of competition between adjoining interspecific colonies of Phragmites and Typha in two large field pilot-scale free water surface (FWS) and subsurface flow (SSF) CWs is evaluated. According to findings, the effect of interspecific competition was notable for Phragmites australis, whereby it showed the highest growth performance in both FWS and SSF wetland. In a mixed-culture, P. australis demonstrates superiority in terms of competitive interactions for space between plants. Furthermore, the inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…In turn, the P content accumulated in the plants in this study (0.08 to 0.19 g P m -2 ) was less than determined by Zheng et al (2016), who found accumulations between 1.5-3.0 g P m -2 .…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In turn, the P content accumulated in the plants in this study (0.08 to 0.19 g P m -2 ) was less than determined by Zheng et al (2016), who found accumulations between 1.5-3.0 g P m -2 .…”
Section: Discussioncontrasting
confidence: 87%
“…Tanner (1996) found a density of 758 stems m -2 in only 90 days from the start of cultivation. Along the same line, biomass production in HSSF was 23% higher than that found by Vymazal and Köpfelová (2005) and Zheng et al (2016) in a CW with Phr production between 500-600 g DW m -2 (first year). Subsequently, stem production in winter (1281 stems m -2 ) matched that determined by Rodríguez and Brisson (2015) and Vymazal and Köpfelová (2005), who observed the development of 1366 stems m -2 in winter (first year) and biomass production between 1000 and 1600 g DW m -2 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Well-developed plants that have a high biomass, are long-standing and have abundant roots in the pond system, which can increase the efficiency of the nutrient uptake and the rhizospheric microbial function for water purification in pond systems [25]. At the end of the experiment, the shrub willow stem biomass was 65.92 ± 3.8 g/plant, accounting for approximately 90% of the total plant biomass, while the roots and the leaves accounted for less than 2% and 9%, respectively.…”
Section: Plant Growth and Nutrient Removalmentioning
confidence: 99%
“…As discussed above, the removal of CC from CTBD in CWs could optimize the efficiency of physicochemical desalination processes. Numerous studies report the removal of, example bulk organics (Konnerup, Koottatep, & Brix, 2009;Neralla, Weaver, Lesikar, & Persyn, 2000), nutrients, such as N and P (Lin, Jing, Wang, & Lee, 2002;Vymazal 2007;Zheng et al, 2016), heavy metals (Khan, Ahmad, Shah, Rehman, & Khaliq, 2009;Maine, Sune, Hadad, S anchez, & Bonetto, 2006), petrochemical constituents (Knight, Kadlec, & Ohlendorf, 1999;Toor, Franz, Fedorak, MacKinnon, & Liber, 2013), and emerging contaminants including pharmaceuticals (Hijosa-Valsero et al, 2011;Li, Zhu, Ng, & Tan, 2014;R€ uhmland, Wick, Ternes, & Barjenbruch, 2015;Zhang et al, 2012), personal care products ( Avila, Nivala et al, 2014;Matamoros & Bayona, 2006;Reyes-Contreras, Matamoros, Ruiz, Soto, & Bayona, 2011), endocrine disruptors ( Avila, Nivala et al, 2014;Avila, Bayona, Mart ın, Salas, & Garc ıa, 2015), and pesticides (Budd, O'Geen, Goh, Bondarenko, & Gan, 2009;Moore et al, 2009) in CWs. Examples of water streams treated by CWs are domestic waste water (Ye & Li, 2009;Zhao et al, 2011), industrial waste water (Chen, Kao, Yeh, Chien, & Chao, 2006;Ji et al, 2002), and surface water streams (Schulz & Peall, 2001;Zhou & Hosomi, 2008).…”
Section: Contaminant Removal Mechanismsmentioning
confidence: 99%